The regulatory effect of 6-TG on lncRNA–miRNA–mRNA ceRNA network in triple-negative breast cancer cell line. Issue 2 (26th February 2021) - Zhang, Daoyu; An, Xinglan; Yu, Hao; Li, Ziyi
Abstract: Breast cancer is one of the most prevalent and recurring cancer types that leads to deaths in women. Triple-negative breast cancer (TNBC) is difficult to treat due to the lack of therapeutic targets. Many studies have focused on identifying drugs for use as alternative treatments for breast cancer. Thioguanine (6-TG) exerts antitumor effects in cancer. Increasing evidence has demonstrated that competitive endogenous ribonucleic acids (ceRNAs) are involved in cancer processes. However, the mechanism by which 6-TG regulates lncRNA–miRNA–mRNAs has not been elucidated. We evaluated the antitumor effect of 6-TG in MDA-MB-231 cells and comprehensively analyzed the RNA-Seq data of MDA-MB-231 cells treated with 6-TG. Our results showed that most tumor pathways were blocked by 6-TG. The hub genes were FN1, FLNA, FLNB, VCL, GSN, MYH10, ACTN4, KDR and EREG, and they were all down-regulated after 6-TG treatment. The coexpression network consisted of 18 microRNAs (miRNAs), 9 long noncoding RNAs (lncRNAs) and 20 mRNAs. Hsa-mir-16-5p and Hsa-mir-335-5p targeted the greatest number of mRNAs in the network. These molecules could bind to PAX8-AS1 and eliminate the inhibition of target mRNA expression. We showed that PAX8-AS1 is the main lncRNA affected by 6-TG and that PAX8-AS1 regulates the hub genes in tumor pathways by competitively binding with miR-16-5p and miR-335-5p .